A composite material for grouting and plugging sudden water in karst pipeline and its use method
By using a composite material of modified expansion matrix material and liquid crosslinking curing agent in karst pipelines, the problems of long initial settling time of grouting materials and difficult to gel organic materials in surge flood disasters were solved, and rapid response and Strong bonding effectively resists the erosion of sudden water rush and ensures the construction safety of underground projects.
Patent Information
- Application Number
- CN202310579533.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-23
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-05-23
AI Technical Summary
During the construction of underground engineering in karst areas, sudden flood disasters were severe. The existing grouting materials were set for too long in the initial setting time during the water-moving grouting, which could not meet the requirements of rapid deposition and early strength. At the same time, organic grouting materials were difficult to gel. High prices and potentially risky to the environment.
A karst pipeline water injection grouting sealing composite material is provided, including a modified expansion matrix material and a liquid crosslinking curing agent. The modified expanded matrix material responds to water to form a three-dimensional network structure skeleton, expanding in volume by more than 300 times, and bonds to the karst pipeline through physical cross-linking reaction to form a agglomerated gel that resists piston slippage.
It has achieved rapid response and strong bonding in karst pipelines, effectively resisted the erosion of sudden water, solved the technical problems of sudden water in karst pipelines, and ensured the construction safety of underground projects.
Smart Images

Figure CN116622348B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of underground engineering grouting materials, in particular to a composite material for grouting and plugging water inrush in a karst pipeline and a use method thereof. Background Art
[0002] With the rapid development of economy and science and technology, my country has become a major country in the development and utilization of underground space. Underground engineering construction has gradually extended to karst areas such as Chongqing, Yunnan, and Guangxi. my country is the country with the largest karst area and the widest distribution in the world. Due to the development of karst and the complex and changeable geological conditions, it is very easy to induce many adverse geological disasters, which pose a great threat to construction. Among them, water disasters in karst areas cause the greatest losses to underground engineering construction. According to relevant statistics, since the 21st century, water disasters in karst areas have become a key issue restricting underground engineering construction. The threats to underground engineering are mainly manifested in casualties and economic losses, damage to the hydrogeological environment, ground collapse and other disasters, secondary disasters and other potential hazards, which seriously restrict the stability and development of my country's economy and society.
[0003] In recent years, in response to the increasingly severe situation of sudden water inrush in underground projects, relevant researchers at home and abroad have developed a large number of grouting materials and put them into engineering applications. For example, inorganic grouting materials such as cement and organic grouting materials such as polyurethane, but the initial and final setting time of traditional silicate cement grouting materials is too long to meet the requirements of rapid setting and early strength of dynamic water grouting; and most organic grouting materials are difficult to gel, relatively expensive, and have certain potential risks to the environment. The limitations of traditional grouting materials restrict their application in dynamic water grouting projects. Summary of the invention
[0004] In view of the needs and shortcomings of current technical development, the present invention provides a composite material for grouting and plugging sudden water inrush in a karst pipeline and a method for using the composite material.
[0005] First, the present invention provides a composite material for grouting and plugging sudden water in karst pipelines. The technical solution adopted to solve the above technical problems is as follows:
[0006] A composite material for grouting and plugging water inrush in a karst pipeline, comprising a granular modified swelling matrix material, or a granular modified swelling matrix material and a liquid cross-linking curing agent, wherein:
[0007] The modified expansion matrix material responds to water and forms a three-dimensional network structure skeleton, achieving a volume expansion of more than 300 times. The preparation process is as follows:
[0008] S1.1. Adding acrylic acid monomer to deionized water to prepare a hydrophilic acrylic acid solution, wherein the mass fraction of acrylic acid monomer in the acrylic acid solution is 20%-60%. If the mass fraction of acrylic acid monomer in the acrylic acid solution exceeds the set range, strong and violent polymerization is likely to occur during the reaction, and the heat cannot evaporate in time to cause molecular weight loss, affecting material properties. If the mass fraction of acrylic acid monomer in the acrylic acid solution is lower than the set range, the percentage of deionized water in the container is greater than the monomer content, and gel reaction cannot occur;
[0009] S1.2, weigh the cross-linking agent and active initiator;
[0010] The amount of crosslinking agent affects the formation of the three-dimensional network structure of the modified expanded matrix material. If the crosslinking degree is low, the three-dimensional network cannot be fully formed, the mechanical properties are poor, and the water retention is poor. Especially when there is external pressure, water is easy to be removed, but the theoretical water storage capacity is large because when it is fully extended, there is more internal space. When the crosslinking degree is high, although the mechanical properties and water retention are good, the water absorption rate may also decrease due to the reduction of water absorption space. Therefore, the amount of crosslinking agent is 0.2%-0.8% of the mass of the acrylic acid solution;
[0011] The initiator is a substance that can initiate the polymerization reaction of monomers. The dosage of the initiator should be appropriate, not too much or too little. If it is too much, the reaction speed will be too fast and difficult to control. If it is too little, it will be difficult to initiate, the reaction cannot proceed normally, and the polymer performance will be affected. Therefore, the dosage of the active initiator is 0.2%-0.5% of the mass of the acrylic acid solution;
[0012] Add a crosslinking agent to the acrylic acid solution in step S1.1, pass nitrogen gas through the solution at a uniform speed to remove oxygen, stir evenly, add an active initiator to carry out polymerization reaction, and obtain a procolloid after the polymerization reaction is completed;
[0013] S1.3, the pre-colloid obtained in step S1.2 is put into a meat grinder and ground, then an alkaline solution is weighed for neutralization, and then the product is sieved and placed in a drying oven for drying to further obtain pre-colloid polymer particles;
[0014] S1.4, weigh a surface crosslinking agent, the amount of which is 2%-5% of the pre-colloidal polymer particles, spray the surface crosslinking agent on the surface of the pre-colloidal polymer particles obtained in step S1.3, stir evenly and put it into a drying oven again for drying to obtain an expanded matrix material;
[0015] S1.5, weigh the natural polymer solution, the amount of which is 1%-5% of the expansion matrix material, and evenly spray the natural polymer solution with active hydrophilic groups on the expansion matrix material obtained in step S1.4, and put it into the drying oven again for drying after uniform stirring to obtain the modified expansion matrix material, and sieve the modified expansion matrix material of different particle sizes as needed for standby use, for example, less than 8 mesh, 8-30 mesh, 30-60 mesh, 60-100 mesh, greater than 100 mesh, etc. As the mesh number increases, the speed of the modified expansion matrix material responding to water is faster, and as the mesh number decreases, the speed of the modified expansion matrix material responding to water is slower. In actual engineering, one or more modified expansion matrix materials of different particle sizes can be selected and pumped into the formation according to the water gushing situation of the karst pipeline.
[0016] The modified expansion matrix material undergoes a physical cross-linking reaction with the cross-linking curing agent, cross-linking the modified expansion matrix material after the response, and bonding the modified expansion matrix material to the karst pipeline in a more solid manner to form an agglomerated gel with anti-piston sliding ability to resist the scouring of sudden water. The preparation process of the cross-linking curing agent is as follows:
[0017] S2.1. Weigh the polyether polyol, place it in a rotary evaporator, and vacuum-dry it at 110-120°C until the water content is less than 0.05%, then take it out for later use;
[0018] S2.2, weighing chain extender, organic solvent, isocyanate, catalyst, the amount of chain extender is 8%-15% of the mass of the dehydrated polyether polyol, the amount of organic solvent is 10%-30% of the mass of the dehydrated polyether polyol, the amount of isocyanate is 20%-30% of the mass of the dehydrated polyether polyol, the amount of catalyst is 3%-5% of the mass of the dehydrated polyether polyol; add the polyether polyol dehydrated in step S2.1 to a dry three-necked flask equipped with a magnetic stirrer, add the hydrophilic chain extender and organic solvent under nitrogen protection and heating conditions of 50-80°C; after reacting for 30-60min, uniformly add isocyanate dropwise, add catalyst, continue to react for 8-15min, and then add organic solvent in an amount of 10%-30% of the mass of the dehydrated polyether polyol again to obtain a system solution, at which time, the isocyanate content in the system solution is 5%-10%;
[0019] S2.3. Weigh a neutralizer, the amount of which is 3%-7% of the mass of the dehydrated polyether polyol; add the neutralizer to the system solution of step S2.2 under the action of high shear force of a magnetic stirrer, adjust the system solution to an alkaline environment, and naturally cool it to 65°C under indoor conditions, then remove the residual organic solvent in the system solution to obtain a cross-linking curing agent.
[0020] Optionally, step S1.2 is performed, and the cross-linking agent is one or more of trimethylolpropane trimethacrylate, 1,4-butylene glycol diacrylate, ethylene glycol dimethacrylate, and N,N-methylenebisacrylamide;
[0021] The active initiator is a redox initiator, which uses the free radicals generated by the electron transfer between the oxidant and the reductant to initiate the polymerization reaction. Its advantages can increase the reaction rate and reduce energy consumption. The redox initiator includes hydrogen peroxide and ascorbic acid in a mass ratio of 1:2.
[0022] Optionally, a polymerization reaction is carried out, and when the solution temperature is between 85° C. and 95° C. and the temperature does not rise any more within 1 minute, the polymerization reaction is determined to be complete, and a procolloid is obtained.
[0023] Optionally, step S1.3 is performed, and the alkaline solution is a sodium hydroxide solution. On the one hand, too much or too little solubility of the sodium hydroxide solution will affect the performance of the matrix material. Too little solubility will increase the water solubility of the pre-colloidal material and reduce the water absorption response rate. Too much solubility will cause a large amount of alkali solution to remain, which is not easy to operate the subsequent synthesis. On the other hand, the neutralization degree affects the internal ion content. The greater the neutralization degree, the stronger the polarity of the hydrophilic group, the greater the content, the higher the water absorption rate, and the better the water retention. However, too strong polarity may affect the polymerization, causing a decrease in molecular weight, etc., and may also make the three-dimensional structure incomplete, or the pore size is too small. The smaller the neutralization degree, the greater the viscosity of the pre-colloid, which is not conducive to the water absorption and expansion performance of the obtained matrix material. Therefore, the mass fraction of sodium hydroxide in the sodium hydroxide solution is 20%-80%, and the neutralization degree is 60%-90%;
[0024] The temperature of the drying oven is set at 110-130°C, and the drying time is set at 30min-120min. By setting this temperature and time, the residual moisture in the pre-colloidal polymer particles can be dried to obtain a material with excellent performance.
[0025] Optionally, the surface crosslinking agent is an organic substance containing a large number of hydroxyl and epoxy groups. The pre-colloidal polymer particles obtained in step S1.3 contain a large number of carboxyl groups, which can react chemically with various groups such as hydroxyl, carboxyl, amino, quaternary ammonium, and epoxy groups. This principle can be used to perform surface chemical grafting on the pre-colloidal polymer particles to improve water absorption performance. The mixed aqueous solution of ethanol, polypropylene glycol, and diglycidyl ether contains a large number of hydroxyl and epoxy groups. Therefore, step S1.4 is performed, and the surface crosslinking agent is a mixed aqueous solution of ethanol, polypropylene glycol, and diglycidyl ether, wherein the mass ratio of ethanol, polypropylene glycol, and diglycidyl ether to water is 3-5:3-5:5-10;
[0026] The temperature of the drying box is set at 110-130°C, and the drying time is set at 30min-120min. Setting this temperature and time can dry out the residual moisture in the expanded matrix material to obtain a material with excellent performance.
[0027] Optionally, the expansion matrix material obtained in step S1.4 is a good donor and acceptor of non-covalent interactions (including hydrogen bonding, electrostatic interaction, and hydrophobic interaction), and can provide multiple non-covalent interaction sites. The expansion matrix material can be modified by utilizing the weak interaction between the expansion matrix material and the natural polymer material. Therefore, step S1.5 is performed, and the natural polymer solution is selected from one or more of chitosan solution, guar gum, and gelatin. Chitosan solution, guar gum, and gelatin have the advantages of low price, simple preparation, and simple operation process;
[0028] The temperature of the drying box is set at 110-130°C, and the drying time is set at 30min-120min. By setting this temperature and time, the residual moisture in the modified expanded matrix material can be dried to obtain a material with excellent performance.
[0029] Optionally, step S2.1 is performed, and the polyether polyol is polyether polyol PEG1000 and polyether polyol PEG2000, and the mass ratio of the two is 1-5:1-5;
[0030] The polyether polyol is placed in a rotary evaporator and dehydrated under vacuum at 110-120° C. for 1.5-2 h.
[0031] Optionally, step S2.2 is performed, the chain extender is dimethylol propionic acid, the organic solvent is acetone solution, and the isocyanate includes Toluene diisocyanate , diphenylmethane diisocyanate, hexamethylene diisocyanate or more, and the catalyst is organic tin.
[0032] Optionally, perform step S2.3, add a neutralizing agent to the system solution of step S2.2 to adjust the pH value of the system solution to between 8 and 9, wherein the neutralizing agent is triethylamine;
[0033] After the system solution is naturally cooled to 65° C., the residual organic solvent in the system solution is removed by reduced pressure distillation to obtain a cross-linking curing agent.
[0034] Secondly, the present invention further provides a method for using a composite material for grouting and plugging sudden water in karst pipelines. The technical solution adopted to solve the above technical problems is as follows:
[0035] A method for using a composite material for grouting and plugging sudden water in a karst pipeline, the use process is as follows:
[0036] (1.1) Select modified expansion matrix materials of different particle sizes as needed and place them in the sudden water in the karst area. The modified expansion matrix materials respond to water and form a three-dimensional network structure skeleton, with the volume expanding by more than 300 times;
[0037] or,
[0038] (2.1) weighing the modified expansion matrix material and the cross-linking curing agent in a mass ratio of 1-4:1-4, weighing anhydrous ethanol in a ratio of 5%-10% of the content of the cross-linking curing agent, and adding the anhydrous ethanol as a diluent to the cross-linking curing agent;
[0039] (2.2) The modified expansive matrix material is placed at the location where sudden water surge occurs in the karst pipeline or water seepage occurs in the lining cracks of the tunnel project. At the same time, the cross-linking curing agent added with anhydrous ethanol is pumped to the location where the modified expansive matrix material is placed. After the two are mixed, a physical cross-linking reaction occurs to form an agglomerated gel with anti-piston sliding ability, namely, a grouting plugging composite material.
[0040] The composite material for grouting and plugging sudden water in a karst pipeline and the use method thereof of the present invention have the following beneficial effects compared with the prior art:
[0041] (1) The modified expansive matrix material in the grouting and plugging composite material of the present invention can respond to water to form a three-dimensional network structure skeleton, thereby achieving a volume expansion of more than 300 times. The cross-linking curing agent and the modified expansive matrix material undergo a physical cross-linking reaction to cross-link the modified expansive matrix material after the response, and bond the modified expansive matrix material to the karst pipeline in a more solid manner to form an agglomerated gel with anti-piston sliding ability to resist the scouring of sudden water, thereby solving the technical difficulties in the sudden water control of karst pipelines, realizing the upgrading of technical means in this field, and ensuring the construction safety of subsequent underground engineering construction.
[0042] (2) When the present invention is actually used for grouting and plugging composite materials, modified expansive matrix materials of different particle sizes can be selected and placed at the location where sudden water gushing occurs in the karst pipeline. As the particle size of the modified expansive matrix material is different, the total mesh number of the modified expansive matrix material required is also different. As the mesh number increases, the speed at which the modified expansive matrix material responds to water becomes faster, and as the mesh number decreases, the speed at which the modified expansive matrix material responds to water becomes slower. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Attached Figure 1 This is a real effect diagram of the modified expansion matrix material prepared by the present invention;
[0044] Attached Figure 2 This is a real effect diagram of the cross-linking curing agent prepared by the present invention;
[0045] Attached Figure 3The figure is a real effect diagram of the response of the composite material for grouting and plugging water inrush in a karst pipeline obtained by mixing the modified expansion matrix material prepared in the other embodiments of the present invention except the first embodiment with a cross-linking curing agent containing anhydrous ethanol after it comes into contact with water;
[0046] Attached Figure 4 yes Figure 3 SEM image of the obtained karst pipeline sudden water grouting plugging composite material after responding to water and then freeze-dried. DETAILED DESCRIPTION
[0047] In order to make the technical solution, the technical problem solved and the technical effect of the present invention more clearly understood, the technical solution of the present invention is clearly and completely described below in conjunction with specific embodiments.
[0048] Embodiment 1:
[0049] Combined with Figure 1 This embodiment proposes a composite material for grouting and plugging sudden water in karst pipelines, including a granular modified expansion matrix material. The modified expansion matrix material responds to water to form a three-dimensional network structure skeleton, achieving a volume expansion of more than 300 times.
[0050] The entire preparation process of the modified expansion matrix material takes place in a fume hood in a room temperature laboratory, and the prepared solution is reacted in a visual thermos cup. The preparation process of the modified expansion matrix material is as follows:
[0051] S1.1. Add acrylic acid monomer to deionized water to prepare 72 parts of hydrophilic acrylic acid solution, wherein the mass fraction of acrylic acid monomer in the acrylic acid solution is 20%. If the mass fraction of acrylic acid monomer in the acrylic acid solution is too high, strong and violent polymerization will easily occur during the reaction, and the heat will not have time to evaporate, resulting in molecular weight loss, affecting material properties. If the mass fraction of acrylic acid monomer in the acrylic acid solution is too low, the percentage of deionized water in the container is greater than the monomer content, and gel reaction cannot occur.
[0052] S1.2, weigh the cross-linking agent. The amount of cross-linking agent affects the formation of the three-dimensional network structure of the modified expansion matrix material. If the cross-linking degree is low, the three-dimensional network cannot be fully formed, the mechanical properties are not good, and the water retention is poor. Especially when there is external pressure, water is easy to be removed, but the theoretical water storage capacity is large, because when it is fully extended, there is more internal space. When the cross-linking degree is high, although the mechanical properties and water retention are good, the water absorption rate may also decrease due to the reduction of water absorption space. Therefore, the amount of cross-linking agent is 0.2%-0.8% of the mass of the acrylic acid solution;
[0053] Weigh the active initiator. The initiator is a substance that can initiate the polymerization reaction of the monomer. The amount of the initiator should be appropriate, not too much or too little. If it is too much, the reaction speed will be too fast and difficult to control. If it is too little, it will be difficult to initiate, the reaction cannot proceed normally, and the polymer performance will be affected. Therefore, the amount of active initiator used is 0.2%-0.5% of the mass of the acrylic acid solution.
[0054] In this embodiment, the crosslinking agent is trimethylolpropane trimethacrylate, and 0.0288 parts of trimethylolpropane trimethacrylate are weighed. The active initiator is a redox initiator, including hydrogen peroxide and ascorbic acid in a mass ratio of 1:2, and 0.72 parts of a hydrogen peroxide and ascorbic acid solution with a mass fraction of 30% are weighed.
[0055] To the acrylic acid solution in step S1.1, add 0.0288 parts of trimethylolpropane trimethacrylate, and remove oxygen in the solution by passing nitrogen at a constant rate of 200 ml / min. After stirring for 3 minutes, add a redox initiator to carry out polymerization reaction. When the solution temperature is between 85°C and 95°C and the temperature does not rise within 1 minute, the polymerization reaction is determined to be complete to obtain a procolloid.
[0056] S1.3. Put the pre-colloid obtained in step S1.2 into a meat grinder and grind it. Then weigh 24 parts of sodium hydroxide solution with a mass fraction of 20% for neutralization. The neutralization degree is controlled at 60%. After screening, the product is placed in a drying oven for drying to obtain pre-colloid polymer particles. During this process, the drying oven temperature is set at 110°C and the drying time is set at 100 minutes. Setting this temperature and time can dry the residual moisture in the pre-colloid polymer particles to obtain a material with excellent performance.
[0057] S1.4. The surface crosslinking agent is a mixed aqueous solution of ethanol, polypropylene glycol and diglycidyl ether, wherein the mass ratio of ethanol, polypropylene glycol, diglycidyl ether and water is 3-5:3-5:5-10. Weigh 5 parts of the mixed aqueous solution of polypropylene glycol diglycidyl ether with a mass fraction of 40%.
[0058] Spray the surface crosslinking agent onto the surface of the pre-colloidal polymer particles obtained in step S1.3, stir evenly and put them into the drying oven for drying again to obtain the expanded matrix material. During this process, the drying oven temperature is set at 100°C and the drying time is set at 60 minutes. Setting this temperature and time can dry the residual moisture in the pre-colloidal polymer particles to obtain a material with excellent performance.
[0059] S1.5, weigh 2.5 parts of natural polymer solution, specifically chitosan solution with a mass fraction of 50%. Spray the chitosan solution with active hydrophilic groups evenly on the expansion matrix material obtained in step S1.4, stir evenly and put it into a drying oven for drying again to obtain a modified expansion matrix material. During this process, the drying oven temperature is set at 110°C and the drying time is set at 120 minutes. Setting this temperature and time can dry the residual water in the pre-colloidal polymer particles to obtain a material with excellent performance.
[0060] The modified expansive matrix materials of different particle sizes are screened for use as needed, such as less than 8 mesh, 8-30 mesh, 30-60 mesh, 60-100 mesh, greater than 100 mesh, etc. As the mesh number increases, the modified expansive matrix material responds faster when it encounters water, and as the mesh number decreases, the modified expansive matrix material responds slower when it encounters water. In actual projects, one or more modified expansive matrix materials of different particle sizes can be selected and pumped into the formation according to the water gushing situation of the karst pipeline.
[0061] The modified expanded matrix material prepared in this embodiment has the following properties:
[0062]
[0063] Regarding the preparation process of the modified expanded matrix material in this embodiment, it is necessary to supplement:
[0064] (i) Step S1.2 is performed. In addition to trimethylolpropane trimethacrylate, the cross-linking agent may also be one or more of 1,4-butylene glycol diacrylate, ethylene glycol dimethacrylate, and N,N-methylenebisacrylamide.
[0065] (ii) The drying oven temperature is set at 110-130° C. and the drying time is set at 30 min-120 min. This temperature and time can be set to dry out the residual moisture in the pre-colloidal polymer particles to obtain a material with excellent properties.
[0066] (iii) The expansion matrix material obtained in step S1.4 is a good donor and acceptor of non-covalent interactions (including hydrogen bonding, electrostatic interaction, and hydrophobic interaction), and can provide multiple non-covalent interaction sites. The expansion matrix material can be modified by utilizing the weak interaction between the expansion matrix material and the natural polymer material. Therefore, in performing step S1.5, in addition to chitosan solution, guar gum and gelatin can also be used as the natural polymer solution. Chitosan solution, guar gum and gelatin have the advantages of low price, simple preparation and simple operation process.
[0067] Embodiment 2:
[0068] Combined with Figure 1-4 This embodiment proposes a composite material for grouting and plugging sudden water inrush in a karst pipeline, comprising a granular modified expansion matrix material and a liquid cross-linking curing agent, wherein: the modified expansion matrix material responds to water to form a three-dimensional network structure skeleton, achieving a volume expansion of more than 300 times, the modified expansion matrix material and the cross-linking curing agent undergo a physical cross-linking reaction, the modified expansion matrix material after the response is cross-linked, and the modified expansion matrix material is bonded to the karst pipeline in a more secure manner to form an agglomerated gel with anti-piston sliding ability to resist the scouring of sudden water inrush.
[0069] The entire preparation process of the modified expansion matrix material takes place in a fume hood in a room temperature laboratory, and the prepared solution is reacted in a visual thermos cup. The preparation process of the modified expansion matrix material is as follows:
[0070] S1.1. Add acrylic acid monomer to deionized water to prepare 72 parts of hydrophilic acrylic acid solution, wherein the mass fraction of acrylic acid monomer in the acrylic acid solution is 20%. If the mass fraction of acrylic acid monomer in the acrylic acid solution is too high, strong and violent polymerization will easily occur during the reaction, and the heat will not have time to evaporate, resulting in molecular weight loss, affecting material properties. If the mass fraction of acrylic acid monomer in the acrylic acid solution is too low, the percentage of deionized water in the container is greater than the monomer content, and gel reaction cannot occur.
[0071] S1.2, weigh the cross-linking agent. The amount of cross-linking agent affects the formation of the three-dimensional network structure of the modified expansion matrix material. If the cross-linking degree is low, the three-dimensional network cannot be fully formed, the mechanical properties are not good, and the water retention is poor. Especially when there is external pressure, water is easy to be removed, but the theoretical water storage capacity is large, because when it is fully extended, there is more internal space. When the cross-linking degree is high, although the mechanical properties and water retention are good, the water absorption rate may also decrease due to the reduction of water absorption space. Therefore, the amount of cross-linking agent is 0.2%-0.8% of the mass of the acrylic acid solution;
[0072] Weigh the active initiator. The initiator is a substance that can initiate the polymerization reaction of the monomer. The amount of the initiator should be appropriate, not too much or too little. If it is too much, the reaction speed will be too fast and difficult to control. If it is too little, it will be difficult to initiate, the reaction cannot proceed normally, and the polymer performance will be affected. Therefore, the amount of active initiator used is 0.2%-0.5% of the mass of the acrylic acid solution.
[0073] In this embodiment, the crosslinking agent is trimethylolpropane trimethacrylate, and 0.0288 parts of trimethylolpropane trimethacrylate are weighed. The active initiator is a redox initiator, including hydrogen peroxide and ascorbic acid in a mass ratio of 1:2, and 0.72 parts of a hydrogen peroxide and ascorbic acid solution with a mass fraction of 30% are weighed.
[0074] To the acrylic acid solution in step S1.1, add 0.0288 parts of trimethylolpropane trimethacrylate, and remove oxygen in the solution by passing nitrogen at a constant rate of 200 ml / min. After stirring for 3 minutes, add a redox initiator to carry out polymerization reaction. When the solution temperature is between 85°C and 95°C and the temperature does not rise within 1 minute, the polymerization reaction is determined to be complete to obtain a procolloid.
[0075] S1.3. Put the pre-colloid obtained in step S1.2 into a meat grinder and grind it. Then weigh 24 parts of sodium hydroxide solution with a mass fraction of 20% for neutralization. The neutralization degree is controlled at 60%. After screening, the product is placed in a drying oven for drying to obtain pre-colloid polymer particles. During this process, the drying oven temperature is set at 110°C and the drying time is set at 100 minutes. Setting this temperature and time can dry the residual moisture in the pre-colloid polymer particles to obtain a material with excellent performance.
[0076] S1.4. The surface crosslinking agent is a mixed aqueous solution of ethanol, polypropylene glycol and diglycidyl ether, wherein the mass ratio of ethanol, polypropylene glycol, diglycidyl ether and water is 3-5:3-5:5-10. Weigh 5 parts of the mixed aqueous solution of polypropylene glycol diglycidyl ether with a mass fraction of 40%.
[0077] Spray the surface crosslinking agent onto the surface of the pre-colloidal polymer particles obtained in step S1.3, stir evenly and put them into the drying oven for drying again to obtain the expanded matrix material. During this process, the drying oven temperature is set at 100°C and the drying time is set at 60 minutes. Setting this temperature and time can dry the residual moisture in the pre-colloidal polymer particles to obtain a material with excellent performance.
[0078] S1.5, weigh 2.5 parts of natural polymer solution, specifically chitosan solution with a mass fraction of 50%. Spray the chitosan solution with active hydrophilic groups evenly on the expansion matrix material obtained in step S1.4, stir evenly and put it into a drying oven for drying again to obtain a modified expansion matrix material. During this process, the drying oven temperature is set at 110°C and the drying time is set at 120 minutes. Setting this temperature and time can dry the residual water in the pre-colloidal polymer particles to obtain a material with excellent performance.
[0079] The modified expansive matrix materials of different particle sizes are screened for use as needed, such as less than 8 mesh, 8-30 mesh, 30-60 mesh, 60-100 mesh, greater than 100 mesh, etc. As the mesh number increases, the modified expansive matrix material responds faster when it encounters water, and as the mesh number decreases, the modified expansive matrix material responds slower when it encounters water. In actual projects, one or more modified expansive matrix materials of different particle sizes can be selected and pumped into the formation according to the water gushing situation of the karst pipeline.
[0080] The modified expanded matrix material prepared in this embodiment has the following properties:
[0081]
[0082] Regarding the preparation process of the modified expanded matrix material in this embodiment, it is necessary to supplement:
[0083] (i) Step S1.2 is performed. In addition to trimethylolpropane trimethacrylate, the cross-linking agent may also be one or more of 1,4-butylene glycol diacrylate, ethylene glycol dimethacrylate, and N,N-methylenebisacrylamide.
[0084] (ii) The drying oven temperature is set at 110-130° C. and the drying time is set at 30 min-120 min. This temperature and time can be set to dry out the residual moisture in the pre-colloidal polymer particles to obtain a material with excellent properties.
[0085] (iii) The expansion matrix material obtained in step S1.4 is a good donor and acceptor of non-covalent interactions (including hydrogen bonding, electrostatic interaction, and hydrophobic interaction), and can provide multiple non-covalent interaction sites. The expansion matrix material can be modified by utilizing the weak interaction between the expansion matrix material and the natural polymer material. Therefore, in performing step S1.5, in addition to chitosan solution, guar gum and gelatin can also be used as the natural polymer solution. Chitosan solution, guar gum and gelatin have the advantages of low price, simple preparation and simple operation process.
[0086] The entire preparation process of the cross-linking curing agent takes place in a fume hood in a normal temperature laboratory, and the reaction is carried out in a dry three-necked flask equipped with a magnetic stirrer. The preparation process of the cross-linking curing agent is as follows:
[0087] S2.1. Weigh 100 parts of polyether polyol, place in a rotary evaporator, and dehydrate under vacuum at 110°C for 1.5 hours until the water content is less than 0.05%, then take out for use.
[0088] S2.2, select dimethylol propionic acid as the chain extender, select acetone solution as the organic solvent, and select organotin as the catalyst. Weigh 8 parts of 50% dimethylol propionic acid, 10 parts of 50% acetone solution, 8 parts of 99.5% acetone solution, and 3 parts of organotin;
[0089] The polyether polyol dehydrated in step S2.1 is added to a dry three-necked flask equipped with a magnetic stirrer, and 8 parts of 50% dihydroxymethylpropionic acid and 10 parts of 50% acetone solution are added under nitrogen protection and heating at 50°C; after reacting for 30 minutes, 20 parts of toluene diisocyanate are added dropwise at a uniform rate, and 3 parts of organic tin are added. After continuing the reaction for 10 minutes, an organic solvent in an amount of 10%-30% of the mass of the dehydrated polyether polyol is added again to reduce the viscosity. Here, the organic solvent is selected as 8 parts of 99.5% acetone solution. Subsequently, a system solution is obtained. At this time, the isocyanate content in the system solution is stabilized at about 5%.
[0090] S2.3. Select triethylamine as a neutralizing agent, add 3.1 parts of triethylamine with a mass fraction of 50% to the system solution of step S2.2 under the action of high shear force of a magnetic stirrer, adjust the system solution to an alkaline environment with a pH value between 8 and 9, and naturally cool it to 65°C under indoor conditions, then remove the residual acetone solution in the system solution by reduced pressure distillation to obtain a cross-linking curing agent.
[0091] The cross-linking curing agent prepared in this embodiment has the following properties:
[0092] Test products Dissolution time of cross-linking curing agent in anhydrous ethanol Cross-linking curing agent 10s
[0093] Regarding the preparation process of the cross-linking curing agent in this embodiment, it is necessary to supplement:
[0094] (i) performing step S2.1, wherein the polyether polyols are polyether polyol PEG1000 and polyether polyol PEG2000, and the mass ratio of the two is 1-5:1-5; the polyether polyols are placed in a rotary evaporator and vacuum-dehydrated at a heating condition of 110-120° C. for 1.5-2 h.
[0095] (ii) Step S2.2 is performed, wherein the isocyanate can be one or more of toluene diisocyanate, diphenylmethane diisocyanate, and hexamethylene diisocyanate.
[0096] The modified expansion matrix material and cross-linking curing agent prepared in this embodiment are used as follows:
[0097] Weigh 50 parts of a modified expansion matrix material having a particle size greater than 100 mesh, weigh 50 parts of a cross-linking curing agent, and 4 parts of anhydrous ethanol, and add the anhydrous ethanol as a diluent to the cross-linking curing agent;
[0098] The modified expansive matrix material is placed at the location where sudden water gushing occurs in the karst pipeline or water seepage occurs in the lining cracks of the tunnel project, and the cross-linking curing agent mixed with anhydrous ethanol is pumped to the placement location of the modified expansive matrix material. After the two are mixed, a physical cross-linking reaction occurs to form an agglomerated gel with anti-piston sliding ability, namely a grouting and plugging composite material.
[0099] Using the modified expansion matrix material and the cross-linking curing agent prepared in this embodiment, the performance of the composite material for grouting and plugging sudden water in karst pipelines is as follows:
[0100]
[0101] Embodiment three:
[0102] Combined with Figure 1-4 This embodiment proposes a composite material for grouting and plugging sudden water inrush in a karst pipeline, comprising a granular modified expansion matrix material and a liquid cross-linking curing agent, wherein: the modified expansion matrix material responds to water to form a three-dimensional network structure skeleton, achieving a volume expansion of more than 300 times, the modified expansion matrix material and the cross-linking curing agent undergo a physical cross-linking reaction, the modified expansion matrix material after the response is cross-linked, and the modified expansion matrix material is bonded to the karst pipeline in a more secure manner to form an agglomerated gel with anti-piston sliding ability to resist the scouring of sudden water inrush.
[0103] The entire preparation process of the modified expansion matrix material takes place in a fume hood in a room temperature laboratory, and the prepared solution is reacted in a visual thermos cup. The preparation process of the modified expansion matrix material is as follows:
[0104] S1.1. Add acrylic acid monomer to deionized water to prepare 72 parts of hydrophilic acrylic acid solution, wherein the mass fraction of acrylic acid monomer in the acrylic acid solution is 40%. If the mass fraction of acrylic acid monomer in the acrylic acid solution is too large, strong and violent polymerization will easily occur during the reaction, and the heat will not have time to evaporate, resulting in molecular weight loss, affecting material properties. If the mass fraction of acrylic acid monomer in the acrylic acid solution is too small, the percentage of deionized water in the container is greater than the monomer content, and gel reaction cannot occur.
[0105] S1.2, weigh the cross-linking agent. The amount of cross-linking agent affects the formation of the three-dimensional network structure of the modified expansion matrix material. If the cross-linking degree is low, the three-dimensional network cannot be fully formed, the mechanical properties are not good, and the water retention is poor. Especially when there is external pressure, water is easy to be removed, but the theoretical water storage capacity is large, because when it is fully extended, there is more internal space. When the cross-linking degree is high, although the mechanical properties and water retention are good, the water absorption rate may also decrease due to the reduction of water absorption space. Therefore, the amount of cross-linking agent is 0.2%-0.8% of the mass of the acrylic acid solution.
[0106] Weigh the active initiator. The initiator is a substance that can initiate the polymerization reaction of the monomer. The amount of the initiator should be appropriate, not too much or too little. If it is too much, the reaction speed will be too fast and difficult to control. If it is too little, it will be difficult to initiate, the reaction cannot proceed normally, and the polymer performance will be affected. Therefore, the amount of active initiator used is 0.2%-0.5% of the mass of the acrylic acid solution.
[0107] In this embodiment, the crosslinking agent is trimethylolpropane trimethacrylate, and 0.06 parts of trimethylolpropane trimethacrylate are weighed. The active initiator is a redox initiator, including hydrogen peroxide and ascorbic acid in a mass ratio of 1:2, and 1.22 parts of a hydrogen peroxide and ascorbic acid solution with a mass fraction of 30% are weighed.
[0108] To the acrylic acid solution in step S1.1, add 0.06 parts of trimethylolpropane trimethacrylate, and remove oxygen in the solution by passing nitrogen at a constant rate of 200 ml / min. After stirring for 3 minutes, add a redox initiator to carry out polymerization reaction. When the solution temperature is between 85°C and 95°C and the temperature does not rise within 1 minute, the polymerization reaction is determined to be complete to obtain a procolloid.
[0109] S1.3. Put the pre-colloid obtained in step S1.2 into a meat grinder and grind it. Then weigh 36 parts of 50% sodium hydroxide solution by mass for neutralization. The degree of neutralization is controlled at 75%. After screening, the product is placed in a drying oven for drying to obtain pre-colloid polymer particles. During this process, the drying oven temperature is set at 110°C and the drying time is set at 120 minutes. Setting this temperature and time can dry the residual moisture in the pre-colloid polymer particles to obtain a material with excellent performance.
[0110] S1.4, the surface crosslinking agent is a mixed aqueous solution of ethanol, polypropylene glycol, and diglycidyl ether, wherein the mass ratio of ethanol, polypropylene glycol, diglycidyl ether to water is 3-5:3-5:5-10, and 8 parts of the mixed aqueous solution of polypropylene glycol diglycidyl ether with a mass fraction of 50% are weighed.
[0111] Spray the surface crosslinking agent onto the surface of the pre-colloidal polymer particles obtained in step S1.3, stir evenly and put them into the drying oven for drying again to obtain the expanded matrix material. During this process, the drying oven temperature is set at 100°C and the drying time is set at 60 minutes. Setting this temperature and time can dry the residual moisture in the pre-colloidal polymer particles to obtain a material with excellent performance.
[0112] S1.5. Weigh 4 parts of natural polymer solution, which is specifically a chitosan solution with a mass fraction of 40%; evenly spray the chitosan solution with active hydrophilic groups on the expansion matrix material obtained in step S1.4, stir evenly and put it into a drying oven for drying again to obtain a modified expansion matrix material. During this process, the drying oven temperature is set at 110°C and the drying time is set at 120 minutes. Setting this temperature and time can dry the residual moisture in the pre-colloidal polymer particles to obtain a material with excellent performance.
[0113] The modified expansive matrix materials of different particle sizes are screened for use as needed, such as less than 8 mesh, 8-30 mesh, 30-60 mesh, 60-100 mesh, greater than 100 mesh, etc. As the mesh number increases, the modified expansive matrix material responds faster when it encounters water, and as the mesh number decreases, the modified expansive matrix material responds slower when it encounters water. In actual projects, one or more modified expansive matrix materials of different particle sizes can be selected and pumped into the formation according to the water gushing situation of the karst pipeline.
[0114] The modified expanded matrix material prepared in this embodiment has the following properties:
[0115]
[0116] Regarding the preparation process of the modified expanded matrix material in this embodiment, it is necessary to supplement:
[0117] (i) Step S1.2 is performed. In addition to trimethylolpropane trimethacrylate, the cross-linking agent may also be one or more of 1,4-butylene glycol diacrylate, ethylene glycol dimethacrylate, and N,N-methylenebisacrylamide.
[0118] (ii) The drying oven temperature is set at 110-130° C. and the drying time is set at 30 min-120 min. This temperature and time can be set to dry out the residual moisture in the pre-colloidal polymer particles to obtain a material with excellent properties.
[0119] (iii) The expansion matrix material obtained in step S1.4 is a good donor and acceptor of non-covalent interactions (including hydrogen bonding, electrostatic interaction, and hydrophobic interaction), and can provide multiple non-covalent interaction sites. The expansion matrix material can be modified by utilizing the weak interaction between the expansion matrix material and the natural polymer material. Therefore, in performing step S1.5, in addition to chitosan solution, guar gum and gelatin can also be used as the natural polymer solution. Chitosan solution, guar gum and gelatin have the advantages of low price, simple preparation and simple operation process.
[0120] The entire preparation process of the cross-linking curing agent takes place in a fume hood in a normal temperature laboratory, and the reaction is carried out in a dry three-necked flask equipped with a magnetic stirrer. The preparation process of the cross-linking curing agent is as follows:
[0121] S2.1, weigh 100.1 parts of polyether polyol, place it in a rotary evaporator, and vacuum dehydrate it at 110℃ for 1.5h until the water content is less than 0.05%, then take it out for use.
[0122] S2.2, select dimethylol propionic acid as the chain extender, select acetone solution as the organic solvent, and select organotin as the catalyst. Weigh 12 parts of 30% dimethylol propionic acid, 15 parts of 40% acetone solution, 12 parts of 99.5% acetone solution, and 5 parts of organotin;
[0123] The polyether polyol dehydrated in step S2.1 is added to a dry three-necked flask equipped with a magnetic stirrer, and 12 parts of 30% dihydroxymethylpropionic acid and 15 parts of 40% acetone solution are added under nitrogen protection and heating at 50°C; after reacting for 30 minutes, 28 parts of toluene diisocyanate are added dropwise at a uniform rate, and 5 parts of organic tin are added. After continuing the reaction for 10 minutes, an organic solvent in an amount of 10%-30% of the mass of the dehydrated polyether polyol is added again to reduce the viscosity. Here, the organic solvent is selected as 12 parts of 99.5% acetone solution. Subsequently, a system solution is obtained. At this time, the isocyanate content in the system solution is stabilized at about 8%.
[0124] S2.3. Select triethylamine as a neutralizing agent, add 5 parts of triethylamine with a mass fraction of 40% to the system solution of step S2.2 under the action of high shear force of a magnetic stirrer, adjust the system solution to an alkaline environment with a pH value between 8 and 9, and naturally cool it to 65°C under indoor conditions, then remove the residual acetone solution in the system solution by reduced pressure distillation to obtain a cross-linking curing agent.
[0125] The cross-linking curing agent prepared in this embodiment has the following properties:
[0126] Test products Dissolution time of cross-linking curing agent in anhydrous ethanol Cross-linking curing agent 19s
[0127] Regarding the preparation process of the cross-linking curing agent in this embodiment, it is necessary to supplement:
[0128] (i) performing step S2.1, wherein the polyether polyols are polyether polyol PEG1000 and polyether polyol PEG2000, and the mass ratio of the two is 1-5:1-5; the polyether polyols are placed in a rotary evaporator and vacuum-dehydrated at a heating condition of 110-120° C. for 1.5-2 h.
[0129] (ii) Step S2.2 is performed, wherein the isocyanate can be one or more of toluene diisocyanate, diphenylmethane diisocyanate, and hexamethylene diisocyanate.
[0130] The modified expansion matrix material and cross-linking curing agent prepared in this embodiment are used as follows:
[0131] Weigh 50 parts of a modified expansion matrix material with a particle size of 60-100 mesh, weigh 50 parts of a cross-linking curing agent, and 5 parts of anhydrous ethanol, and add the anhydrous ethanol as a diluent to the cross-linking curing agent;
[0132] The modified expansive matrix material is placed at the location where sudden water gushing occurs in the karst pipeline or water seepage occurs in the lining cracks of the tunnel project, and the cross-linking curing agent mixed with anhydrous ethanol is pumped to the placement location of the modified expansive matrix material. After the two are mixed, a physical cross-linking reaction occurs to form an agglomerated gel with anti-piston sliding ability, namely a grouting and plugging composite material.
[0133] Using the modified expansion matrix material and the cross-linking curing agent prepared in this embodiment, the performance of the composite material for grouting and plugging sudden water in karst pipelines is as follows:
[0134]
[0135] Embodiment 4:
[0136] Combined with Figure 1-4 This embodiment proposes a composite material for grouting and plugging sudden water inrush in a karst pipeline, comprising a granular modified expansion matrix material and a liquid cross-linking curing agent, wherein: the modified expansion matrix material responds to water to form a three-dimensional network structure skeleton, achieving a volume expansion of more than 300 times, the modified expansion matrix material and the cross-linking curing agent undergo a physical cross-linking reaction, the modified expansion matrix material after the response is cross-linked, and the modified expansion matrix material is bonded to the karst pipeline in a more secure manner to form an agglomerated gel with anti-piston sliding ability to resist the scouring of sudden water inrush.
[0137] The entire preparation process of the modified expansion matrix material takes place in a fume hood in a room temperature laboratory, and the prepared solution is reacted in a visual thermos cup. The preparation process of the modified expansion matrix material is as follows:
[0138] S1.1. Add acrylic acid monomer to deionized water to prepare 72 parts of hydrophilic acrylic acid solution, wherein the mass fraction of acrylic acid monomer in the acrylic acid solution is 50%. If the mass fraction of acrylic acid monomer in the acrylic acid solution is too large, strong and violent polymerization will easily occur during the reaction, and the heat will not have time to evaporate, resulting in molecular weight loss, affecting material properties. If the mass fraction of acrylic acid monomer in the acrylic acid solution is too small, the percentage of deionized water in the container is greater than the monomer content, and gel reaction cannot occur.
[0139] S1.2, weigh the cross-linking agent. The amount of cross-linking agent affects the formation of the three-dimensional network structure of the modified expansion matrix material. If the cross-linking degree is low, the three-dimensional network cannot be fully formed, the mechanical properties are not good, and the water retention is poor. Especially when there is external pressure, water is easy to be removed, but the theoretical water storage capacity is large, because when it is fully extended, there is more internal space. When the cross-linking degree is high, although the mechanical properties and water retention are good, the water absorption rate may also decrease due to the reduction of water absorption space. Therefore, the amount of cross-linking agent is 0.2%-0.8% of the mass of the acrylic acid solution.
[0140] Weigh the active initiator. The initiator is a substance that can initiate the polymerization reaction of the monomer. The amount of the initiator should be appropriate, not too much or too little. If it is too much, the reaction speed will be too fast and difficult to control. If it is too little, it will be difficult to initiate, the reaction cannot proceed normally, and the polymer performance will be affected. Therefore, the amount of active initiator used is 0.2%-0.5% of the mass of the acrylic acid solution.
[0141] In this embodiment, the crosslinking agent is trimethylolpropane trimethacrylate, and 0.08 parts of trimethylolpropane trimethacrylate are weighed. The active initiator is a redox initiator, including hydrogen peroxide and ascorbic acid in a mass ratio of 1:2, and 1.22 parts of a hydrogen peroxide and ascorbic acid solution with a mass fraction of 40% are weighed.
[0142] To the acrylic acid solution in step S1.1, add 0.08 parts of trimethylolpropane trimethacrylate, and remove oxygen in the solution by passing nitrogen at a constant rate of 200 ml / min. After stirring for 3 minutes, add a redox initiator to carry out polymerization reaction. When the solution temperature is between 85°C and 95°C and the temperature does not rise within 1 minute, the polymerization reaction is determined to be complete to obtain a procolloid.
[0143] S1.3. Put the pre-colloid obtained in step S1.2 into a meat grinder and grind it. Then weigh 36 parts of sodium hydroxide solution with a mass fraction of 40% for neutralization. The neutralization degree is controlled at 80%. After screening, the product is placed in a drying oven for drying to obtain pre-colloid polymer particles. During this process, the drying oven temperature is set at 110°C and the drying time is set at 120 minutes. Setting this temperature and time can dry the residual moisture in the pre-colloid polymer particles to obtain a material with excellent performance.
[0144] S1.4. The surface crosslinking agent is a mixed aqueous solution of ethanol, polypropylene glycol and diglycidyl ether, wherein the mass ratio of ethanol, polypropylene glycol, diglycidyl ether and water is 3-5:3-5:5-10. Weigh 10 parts of the mixed aqueous solution of polypropylene glycol diglycidyl ether with a mass fraction of 40%.
[0145] Spray the surface crosslinking agent onto the surface of the pre-colloidal polymer particles obtained in step S1.3, stir evenly and put them into the drying oven for drying again to obtain the expanded matrix material. During this process, the drying oven temperature is set at 100°C and the drying time is set at 60 minutes. Setting this temperature and time can dry the residual moisture in the pre-colloidal polymer particles to obtain a material with excellent performance.
[0146] S1.5. Weigh 6 parts of natural polymer solution, which is specifically a chitosan solution with a mass fraction of 30%; evenly spray the chitosan solution with active hydrophilic groups on the expansion matrix material obtained in step S1.4, stir evenly and put it into a drying oven for drying again to obtain a modified expansion matrix material. During this process, the drying oven temperature is set at 110°C and the drying time is set at 120 minutes. Setting this temperature and time can dry the residual moisture in the pre-colloidal polymer particles to obtain a material with excellent performance.
[0147] The modified expansive matrix materials of different particle sizes are screened for use as needed, such as less than 8 mesh, 8-30 mesh, 30-60 mesh, 60-100 mesh, greater than 100 mesh, etc. As the mesh number increases, the modified expansive matrix material responds faster when it encounters water, and as the mesh number decreases, the modified expansive matrix material responds slower when it encounters water. In actual projects, one or more modified expansive matrix materials of different particle sizes can be selected and pumped into the formation according to the water gushing situation of the karst pipeline.
[0148] The modified expanded matrix material prepared in this embodiment has the following properties:
[0149]
[0150] Regarding the preparation process of the modified expanded matrix material in this embodiment, it is necessary to supplement:
[0151] (i) Step S1.2 is performed. In addition to trimethylolpropane trimethacrylate, the cross-linking agent may also be one or more of 1,4-butylene glycol diacrylate, ethylene glycol dimethacrylate, and N,N-methylenebisacrylamide.
[0152] (ii) The drying oven temperature is set at 110-130° C. and the drying time is set at 30 min-120 min. This temperature and time can be set to dry out the residual moisture in the pre-colloidal polymer particles to obtain a material with excellent properties.
[0153] (iii) The expansion matrix material obtained in step S1.4 is a good donor and acceptor of non-covalent interactions (including hydrogen bonding, electrostatic interaction, and hydrophobic interaction), and can provide multiple non-covalent interaction sites. The expansion matrix material can be modified by utilizing the weak interaction between the expansion matrix material and the natural polymer material. Therefore, in performing step S1.5, in addition to chitosan solution, guar gum and gelatin can also be used as the natural polymer solution. Chitosan solution, guar gum and gelatin have the advantages of low price, simple preparation and simple operation process.
[0154] The entire preparation process of the cross-linking curing agent takes place in a fume hood in a normal temperature laboratory, and the reaction is carried out in a dry three-necked flask equipped with a magnetic stirrer. The preparation process of the cross-linking curing agent is as follows:
[0155] S2.1. Weigh 100.1 parts of polyether polyol, place in a rotary evaporator, and dehydrate under vacuum at 110° C. for 1.5 h until the water content is less than 0.05%, then take out for later use.
[0156] S2.2, select dimethylol propionic acid as the chain extender, select acetone solution as the organic solvent, and select organotin as the catalyst. Weigh 9.6 parts of 40% dimethylol propionic acid, 12.2 parts of 50% acetone solution, 10 parts of 99.5% acetone solution, and 3.8 parts of organotin;
[0157] The polyether polyol dehydrated in step S2.1 is added to a dry three-necked flask equipped with a magnetic stirrer, and 9.6 parts of 40% dihydroxymethylpropionic acid and 12.2 parts of 50% acetone solution are added under nitrogen protection and heating at 50°C; after reacting for 30 minutes, 32.4 parts of toluene diisocyanate are added dropwise at a uniform rate, and 3.8 parts of organic tin are added. After continuing the reaction for 10 minutes, an organic solvent in an amount of 10%-30% of the mass of the dehydrated polyether polyol is added again to reduce the viscosity. Here, the organic solvent is selected as 10 parts of 99.5% acetone solution. Subsequently, a system solution is obtained. At this time, the isocyanate content in the system solution is stabilized at about 8%.
[0158] S2.3. Select triethylamine as a neutralizing agent, add 6.3 parts of triethylamine with a mass fraction of 50% to the system solution of step S2.2 under the action of high shear force of a magnetic stirrer, adjust the system solution to an alkaline environment with a pH value between 8 and 9, and naturally cool it to 65°C under indoor conditions, then remove the residual acetone solution in the system solution by reduced pressure distillation to obtain a cross-linking curing agent.
[0159] The cross-linking curing agent prepared in this embodiment has the following properties:
[0160] Test products Dissolution time of cross-linking curing agent in anhydrous ethanol Cross-linking curing agent 23s
[0161] Regarding the preparation process of the cross-linking curing agent in this embodiment, it is necessary to supplement:
[0162] (i) performing step S2.1, wherein the polyether polyols are polyether polyol PEG1000 and polyether polyol PEG2000, and the mass ratio of the two is 1-5:1-5; the polyether polyols are placed in a rotary evaporator and vacuum-dehydrated at a heating condition of 110-120° C. for 1.5-2 h.
[0163] (ii) Step S2.2 is performed, wherein the isocyanate can be one or more of toluene diisocyanate, diphenylmethane diisocyanate, and hexamethylene diisocyanate.
[0164] The modified expansion matrix material and cross-linking curing agent prepared in this embodiment are used as follows:
[0165] Weigh 50 parts of a modified expansion matrix material with a particle size of 30-60 mesh, weigh 50 parts of a cross-linking curing agent, and 8 parts of anhydrous ethanol, and add the anhydrous ethanol as a diluent to the cross-linking curing agent;
[0166] The modified expansive matrix material is placed at the location where sudden water gushing occurs in the karst pipeline or water seepage occurs in the lining cracks of the tunnel project, and the cross-linking curing agent mixed with anhydrous ethanol is pumped to the placement location of the modified expansive matrix material. After the two are mixed, a physical cross-linking reaction occurs to form an agglomerated gel with anti-piston sliding ability, namely a grouting and plugging composite material.
[0167] Using the modified expansion matrix material and the cross-linking curing agent prepared in this embodiment, the performance of the composite material for grouting and plugging sudden water in karst pipelines is as follows:
[0168]
[0169] Embodiment five:
[0170] Combined with Figure 1-4 This embodiment proposes a composite material for grouting and plugging sudden water inrush in a karst pipeline, comprising a granular modified expansion matrix material and a liquid cross-linking curing agent, wherein: the modified expansion matrix material responds to water to form a three-dimensional network structure skeleton, achieving a volume expansion of more than 300 times, the modified expansion matrix material and the cross-linking curing agent undergo a physical cross-linking reaction, the modified expansion matrix material after the response is cross-linked, and the modified expansion matrix material is bonded to the karst pipeline in a more secure manner to form an agglomerated gel with anti-piston sliding ability to resist the scouring of sudden water inrush.
[0171] The entire preparation process of the modified expansion matrix material takes place in a fume hood in a room temperature laboratory, and the prepared solution is reacted in a visual thermos cup. The preparation process of the modified expansion matrix material is as follows:
[0172] S1.1. Add acrylic acid monomer to deionized water to prepare 72 parts of hydrophilic acrylic acid solution, wherein the mass fraction of acrylic acid monomer in the acrylic acid solution is 60%. If the mass fraction of acrylic acid monomer in the acrylic acid solution is too large, strong and violent polymerization will easily occur during the reaction, and the heat will not have time to evaporate, resulting in molecular weight loss, affecting material properties. If the mass fraction of acrylic acid monomer in the acrylic acid solution is too small, the percentage of deionized water in the container is greater than the monomer content, and gel reaction cannot occur.
[0173] S1.2, weigh the cross-linking agent. The amount of cross-linking agent affects the formation of the three-dimensional network structure of the modified expansion matrix material. If the cross-linking degree is low, the three-dimensional network cannot be fully formed, the mechanical properties are not good, and the water retention is poor. Especially when there is external pressure, water is easy to be removed, but the theoretical water storage capacity is large, because when it is fully extended, there is more internal space. When the cross-linking degree is high, although the mechanical properties and water retention are good, the water absorption rate may also decrease due to the reduction of water absorption space. Therefore, the amount of cross-linking agent is 0.2%-0.8% of the mass of the acrylic acid solution.
[0174] Weigh the active initiator. The initiator is a substance that can initiate the polymerization reaction of the monomer. The amount of the initiator should be appropriate, not too much or too little. If it is too much, the reaction speed will be too fast and difficult to control. If it is too little, it will be difficult to initiate, the reaction cannot proceed normally, and the polymer performance will be affected. Therefore, the amount of active initiator used is 0.2%-0.5% of the mass of the acrylic acid solution.
[0175] In this embodiment, the crosslinking agent is trimethylolpropane trimethacrylate, and 0.06 parts of trimethylolpropane trimethacrylate are weighed. The active initiator is a redox initiator, including hydrogen peroxide and ascorbic acid in a mass ratio of 1:2, and 1.68 parts of a hydrogen peroxide and ascorbic acid solution with a mass fraction of 35% are weighed.
[0176] 0.06 parts of trimethylolpropane trimethacrylate was added to the acrylic acid solution in step S1.1, and nitrogen was passed through the solution at a constant rate of 200 ml / min to remove oxygen in the solution. After stirring for 3 minutes, a redox initiator was added to carry out polymerization reaction. When the solution temperature was between 85°C and 95°C and the temperature did not rise within 1 minute, the polymerization reaction was determined to be complete, and a procolloid was obtained.
[0177] S1.3. Put the pre-colloid obtained in step S1.2 into a meat grinder and grind it. Then weigh 48 parts of 50% sodium hydroxide solution by mass for neutralization. The degree of neutralization is controlled at 70%. After screening, the product is placed in a drying oven for drying to obtain pre-colloid polymer particles. During this process, the drying oven temperature is set at 110°C and the drying time is set at 120 minutes. Setting this temperature and time can dry the residual moisture in the pre-colloid polymer particles to obtain a material with excellent performance.
[0178] S1.4. The surface crosslinking agent is a mixed aqueous solution of ethanol, polypropylene glycol and diglycidyl ether, wherein the mass ratio of ethanol, polypropylene glycol, diglycidyl ether and water is 3-5:3-5:5-10. Weigh 8 parts of the mixed aqueous solution of polypropylene glycol diglycidyl ether with a mass fraction of 40%.
[0179] Spray the surface crosslinking agent onto the surface of the pre-colloidal polymer particles obtained in step S1.3, stir evenly and put them into the drying oven for drying again to obtain the expanded matrix material. During this process, the drying oven temperature is set at 100°C and the drying time is set at 60 minutes. Setting this temperature and time can dry the residual moisture in the pre-colloidal polymer particles to obtain a material with excellent performance.
[0180] S1.5. Weigh 3 parts of natural polymer solution, which is specifically a chitosan solution with a mass fraction of 40%; evenly spray the chitosan solution with active hydrophilic groups on the expansion matrix material obtained in step S1.4, stir evenly and put it into a drying oven for drying again to obtain a modified expansion matrix material. During this process, the drying oven temperature is set at 110°C and the drying time is set at 120 minutes. Setting this temperature and time can dry the residual moisture in the pre-colloidal polymer particles to obtain a material with excellent performance.
[0181] The modified expansive matrix materials of different particle sizes are screened for use as needed, such as less than 8 mesh, 8-30 mesh, 30-60 mesh, 60-100 mesh, greater than 100 mesh, etc. As the mesh number increases, the modified expansive matrix material responds faster when it encounters water, and as the mesh number decreases, the modified expansive matrix material responds slower when it encounters water. In actual projects, one or more modified expansive matrix materials of different particle sizes can be selected and pumped into the formation according to the water gushing situation of the karst pipeline.
[0182] The modified expanded matrix material prepared in this embodiment has the following properties:
[0183]
[0184] Regarding the preparation process of the modified expanded matrix material in this embodiment, it is necessary to supplement:
[0185] (i) Step S1.2 is performed. In addition to trimethylolpropane trimethacrylate, the cross-linking agent may also be one or more of 1,4-butylene glycol diacrylate, ethylene glycol dimethacrylate, and N,N-methylenebisacrylamide.
[0186] (ii) The drying oven temperature is set at 110-130° C. and the drying time is set at 30 min-120 min. This temperature and time can be set to dry out the residual moisture in the pre-colloidal polymer particles to obtain a material with excellent properties.
[0187] (iii) The expansion matrix material obtained in step S1.4 is a good donor and acceptor of non-covalent interactions (including hydrogen bonding, electrostatic interaction, and hydrophobic interaction), and can provide multiple non-covalent interaction sites. The expansion matrix material can be modified by utilizing the weak interaction between the expansion matrix material and the natural polymer material. Therefore, in performing step S1.5, in addition to chitosan solution, guar gum and gelatin can also be used as the natural polymer solution. Chitosan solution, guar gum and gelatin have the advantages of low price, simple preparation and simple operation process.
[0188] The entire preparation process of the cross-linking curing agent takes place in a fume hood in a normal temperature laboratory, and the reaction is carried out in a dry three-necked flask equipped with a magnetic stirrer. The preparation process of the cross-linking curing agent is as follows:
[0189] S2.1, weigh 100.1 parts of polyether polyol, place it in a rotary evaporator, and vacuum dehydrate it at 110℃ for 1.5h until the water content is less than 0.05%, then take it out for use.
[0190] S2.2, select dimethylol propionic acid as the chain extender, select acetone solution as the organic solvent, and select organotin as the catalyst. Weigh 10.2 parts of 40% dimethylol propionic acid, 18.1 parts of 50% acetone solution, 15 parts of 99.5% acetone solution, and 5 parts of organotin.
[0191] The polyether polyol dehydrated in step S2.1 is added to a dry three-necked flask equipped with a magnetic stirrer, and 10.2 parts of 40% dihydroxymethylpropionic acid and 18.1 parts of 50% acetone solution are added under nitrogen protection and heating at 50°C; after reacting for 30 minutes, 44 parts of toluene diisocyanate are added dropwise at a uniform rate, and 5 parts of organic tin are added. After continuing the reaction for 10 minutes, an organic solvent in an amount of 10%-30% of the mass of the dehydrated polyether polyol is added again to reduce the viscosity. Here, the organic solvent is selected as 15 parts of 99.5% acetone solution. Subsequently, a system solution is obtained. At this time, the isocyanate content in the system solution is stabilized at about 5%.
[0192] S2.3. Select triethylamine as a neutralizing agent, add 4.8 parts of triethylamine with a mass fraction of 50% to the system solution of step S2.2 under the action of high shear force of a magnetic stirrer, adjust the system solution to an alkaline environment with a pH value between 8 and 9, and naturally cool it to 65°C under indoor conditions, then remove the residual acetone solution in the system solution by reduced pressure distillation to obtain a cross-linking curing agent.
[0193] The cross-linking curing agent prepared in this embodiment has the following properties:
[0194] Test products Dissolution time of cross-linking curing agent in anhydrous ethanol Cross-linking curing agent 25s
[0195] Regarding the preparation process of the cross-linking curing agent in this embodiment, it is necessary to supplement:
[0196] (i) performing step S2.1, wherein the polyether polyols are polyether polyol PEG1000 and polyether polyol PEG2000, and the mass ratio of the two is 1-5:1-5; the polyether polyols are placed in a rotary evaporator and vacuum-dehydrated at a heating condition of 110-120° C. for 1.5-2 h.
[0197] (ii) Step S2.2 is performed, wherein the isocyanate can be one or more of toluene diisocyanate, diphenylmethane diisocyanate, and hexamethylene diisocyanate.
[0198] The modified expansion matrix material and cross-linking curing agent prepared in this embodiment are used as follows:
[0199] Weigh 20 parts of a modified expansion matrix material with a particle size of 30-60 mesh, weigh 80 parts of a cross-linking curing agent, and 8 parts of anhydrous ethanol, and add the anhydrous ethanol as a diluent to the cross-linking curing agent;
[0200] The modified expansive matrix material is placed at the location where sudden water gushing occurs in the karst pipeline or water seepage occurs in the lining cracks of the tunnel project, and the cross-linking curing agent mixed with anhydrous ethanol is pumped to the placement location of the modified expansive matrix material. After the two are mixed, a physical cross-linking reaction occurs to form an agglomerated gel with anti-piston sliding ability, namely a grouting and plugging composite material.
[0201] Using the modified expansion matrix material and the cross-linking curing agent prepared in this embodiment, the performance of the composite material for grouting and plugging sudden water in karst pipelines is as follows:
[0202]
[0203] Embodiment six:
[0204] Combined with Figure 1-4This embodiment proposes a composite material for grouting and plugging sudden water inrush in a karst pipeline, comprising a granular modified expansion matrix material and a liquid cross-linking curing agent, wherein: the modified expansion matrix material responds to water to form a three-dimensional network structure skeleton, achieving a volume expansion of more than 300 times, the modified expansion matrix material and the cross-linking curing agent undergo a physical cross-linking reaction, the modified expansion matrix material after the response is cross-linked, and the modified expansion matrix material is bonded to the karst pipeline in a more secure manner to form an agglomerated gel with anti-piston sliding ability to resist the scouring of sudden water inrush.
[0205] The entire preparation process of the modified expansion matrix material takes place in a fume hood in a room temperature laboratory, and the prepared solution is reacted in a visual thermos cup. The preparation process of the modified expansion matrix material is as follows:
[0206] S1.1. Add acrylic acid monomer to deionized water to prepare 72 parts of hydrophilic acrylic acid solution, wherein the mass fraction of acrylic acid monomer in the acrylic acid solution is 40%. If the mass fraction of acrylic acid monomer in the acrylic acid solution is too large, strong and violent polymerization will easily occur during the reaction, and the heat will not have time to evaporate, resulting in molecular weight loss, affecting material properties. If the mass fraction of acrylic acid monomer in the acrylic acid solution is too small, the percentage of deionized water in the container is greater than the monomer content, and gel reaction cannot occur.
[0207] S1.2, weigh the cross-linking agent. The amount of cross-linking agent affects the formation of the three-dimensional network structure of the modified expansion matrix material. If the cross-linking degree is low, the three-dimensional network cannot be fully formed, the mechanical properties are not good, and the water retention is poor. Especially when there is external pressure, water is easy to be removed, but the theoretical water storage capacity is large, because when it is fully extended, there is more internal space. When the cross-linking degree is high, although the mechanical properties and water retention are good, the water absorption rate may also decrease due to the reduction of water absorption space. Therefore, the amount of cross-linking agent is 0.2%-0.8% of the mass of the acrylic acid solution.
[0208] Weigh the active initiator. The initiator is a substance that can initiate the polymerization reaction of the monomer. The amount of the initiator should be appropriate, not too much or too little. If it is too much, the reaction speed will be too fast and difficult to control. If it is too little, it will be difficult to initiate, the reaction cannot proceed normally, and the polymer performance will be affected. Therefore, the amount of active initiator used is 0.2%-0.5% of the mass of the acrylic acid solution.
[0209] In this embodiment, the crosslinking agent is trimethylolpropane trimethacrylate, and 1.41 parts of trimethylolpropane trimethacrylate are weighed. The active initiator is a redox initiator, including hydrogen peroxide and ascorbic acid in a mass ratio of 1:2, and 1.89 parts of a hydrogen peroxide and ascorbic acid solution with a mass fraction of 50% are weighed.
[0210] 1.41 parts of trimethylolpropane trimethacrylate was added to the acrylic acid solution in step S1.1, and nitrogen was passed through the solution at a constant rate of 200 ml / min to remove oxygen. After stirring for 3 minutes, a redox initiator was added to carry out polymerization reaction. When the solution temperature was between 85°C and 95°C and the temperature did not rise within 1 minute, the polymerization reaction was determined to be complete, and a procolloid was obtained.
[0211] S1.3. Put the pre-colloid obtained in step S1.2 into a meat grinder and grind it. Then weigh 36 parts of sodium hydroxide solution with a mass fraction of 40% for neutralization. The neutralization degree is controlled at 65%. After the product is screened, it is placed in a drying oven for drying to obtain pre-colloid polymer particles. During this process, the drying oven temperature is set at 110°C and the drying time is set at 120 minutes. Setting this temperature and time can dry the residual moisture in the pre-colloid polymer particles to obtain a material with excellent performance.
[0212] S1.4. The surface crosslinking agent is a mixed aqueous solution of ethanol, polypropylene glycol and diglycidyl ether, wherein the mass ratio of ethanol, polypropylene glycol, diglycidyl ether and water is 3-5:3-5:5-10. Weigh 6 parts of the mixed aqueous solution of polypropylene glycol diglycidyl ether with a mass fraction of 60%.
[0213] Spray the surface crosslinking agent onto the surface of the pre-colloidal polymer particles obtained in step S1.3, stir evenly and put them into the drying oven for drying again to obtain the expanded matrix material. During this process, the drying oven temperature is set at 100°C and the drying time is set at 60 minutes. Setting this temperature and time can dry the residual moisture in the pre-colloidal polymer particles to obtain a material with excellent performance.
[0214] S1.5. Weigh 3.2 parts of natural polymer solution, which is specifically a chitosan solution with a mass fraction of 50%; evenly spray the chitosan solution with active hydrophilic groups on the expansion matrix material obtained in step S1.4, stir evenly and put it into a drying oven for drying again to obtain a modified expansion matrix material. During this process, the drying oven temperature is set at 110°C and the drying time is set at 120 minutes. Setting this temperature and time can dry the residual moisture in the pre-colloidal polymer particles to obtain a material with excellent performance.
[0215] The modified expansive matrix materials of different particle sizes are screened for use as needed, such as less than 8 mesh, 8-30 mesh, 30-60 mesh, 60-100 mesh, greater than 100 mesh, etc. As the mesh number increases, the modified expansive matrix material responds faster when it encounters water, and as the mesh number decreases, the modified expansive matrix material responds slower when it encounters water. In actual projects, one or more modified expansive matrix materials of different particle sizes can be selected and pumped into the formation according to the water gushing situation of the karst pipeline.
[0216] The modified expanded matrix material prepared in this embodiment has the following properties:
[0217]
[0218]
[0219] Regarding the preparation process of the modified expanded matrix material in this embodiment, it is necessary to supplement:
[0220] (i) Step S1.2 is performed. In addition to trimethylolpropane trimethacrylate, the cross-linking agent may also be one or more of 1,4-butylene glycol diacrylate, ethylene glycol dimethacrylate, and N,N-methylenebisacrylamide.
[0221] (ii) The drying oven temperature is set at 110-130° C. and the drying time is set at 30 min-120 min. This temperature and time can be set to dry out the residual moisture in the pre-colloidal polymer particles to obtain a material with excellent properties.
[0222] (iii) The expansion matrix material obtained in step S1.4 is a good donor and acceptor of non-covalent interactions (including hydrogen bonding, electrostatic interaction, and hydrophobic interaction), and can provide multiple non-covalent interaction sites. The expansion matrix material can be modified by utilizing the weak interaction between the expansion matrix material and the natural polymer material. Therefore, in performing step S1.5, in addition to chitosan solution, guar gum and gelatin can also be used as the natural polymer solution. Chitosan solution, guar gum and gelatin have the advantages of low price, simple preparation and simple operation process.
[0223] The entire preparation process of the cross-linking curing agent takes place in a fume hood in a normal temperature laboratory, and the reaction is carried out in a dry three-necked flask equipped with a magnetic stirrer. The preparation process of the cross-linking curing agent is as follows:
[0224] S2.1. Weigh 100.1 parts of polyether polyol, place in a rotary evaporator, and dehydrate under vacuum at 110° C. for 1.5 h until the water content is less than 0.05%, then take out for later use.
[0225] S2.2, select dimethylol propionic acid as the chain extender, select acetone solution as the organic solvent, and select organotin as the catalyst. Weigh 8.1 parts of 40% dimethylol propionic acid, 28.2 parts of 50% acetone solution, 8 parts of 99.5% acetone solution, and 3.3 parts of organotin.
[0226] The polyether polyol dehydrated in step S2.1 is added to a dry three-necked flask equipped with a magnetic stirrer, and 8.1 parts of 40% dihydroxymethylpropionic acid and 28.2 parts of 50% acetone solution are added under nitrogen protection and heating at 50°C; after reacting for 30 minutes, 26 parts of toluene diisocyanate are added dropwise at a uniform rate, and 3.3 parts of organic tin are added. After continuing the reaction for 10 minutes, an organic solvent in an amount of 10%-30% of the mass of the dehydrated polyether polyol is added again to reduce the viscosity. Here, the organic solvent is selected as 8 parts of 99.5% acetone solution. Subsequently, a system solution is obtained. At this time, the isocyanate content in the system solution is stabilized at about 5%.
[0227] S2.3. Select triethylamine as a neutralizing agent, add 6.5 parts of triethylamine with a mass fraction of 50% to the system solution of step S2.2 under the action of high shear force of a magnetic stirrer, adjust the system solution to an alkaline environment with a pH value between 8 and 9, and naturally cool it to 65°C under indoor conditions, then remove the residual acetone solution in the system solution by reduced pressure distillation to obtain a cross-linking curing agent.
[0228] The cross-linking curing agent prepared in this embodiment has the following properties:
[0229] Test products Dissolution time of cross-linking curing agent in anhydrous ethanol Cross-linking curing agent 17s
[0230] Regarding the preparation process of the cross-linking curing agent in this embodiment, it is necessary to supplement:
[0231] (i) performing step S2.1, wherein the polyether polyols are polyether polyol PEG1000 and polyether polyol PEG2000, and the mass ratio of the two is 1-5:1-5; the polyether polyols are placed in a rotary evaporator and vacuum-dehydrated at a heating condition of 110-120° C. for 1.5-2 h.
[0232] (ii) Step S2.2 is performed, wherein the isocyanate can be one or more of toluene diisocyanate, diphenylmethane diisocyanate, and hexamethylene diisocyanate.
[0233] The modified expansion matrix material and cross-linking curing agent prepared in this embodiment are used as follows:
[0234] Weigh 80 parts of a modified expansion matrix material having a particle size greater than 100 mesh, weigh 20 parts of a cross-linking curing agent, and 6 parts of anhydrous ethanol, and add the anhydrous ethanol as a diluent to the cross-linking curing agent;
[0235] The modified expansive matrix material is placed at the location where sudden water gushing occurs in the karst pipeline or water seepage occurs in the lining cracks of the tunnel project, and the cross-linking curing agent mixed with anhydrous ethanol is pumped to the placement location of the modified expansive matrix material. After the two are mixed, a physical cross-linking reaction occurs to form an agglomerated gel with anti-piston sliding ability, namely a grouting and plugging composite material.
[0236] Using the modified expansion matrix material and the cross-linking curing agent prepared in this embodiment, the performance of the composite material for grouting and plugging sudden water in karst pipelines is as follows:
[0237]
Claims
1. A composite material for grouting and plugging sudden water in karst pipelines, characterized in that: The grouting plugging composite material comprises a granular modified expansion matrix material, or a granular modified expansion matrix material and a liquid cross-linking curing agent, wherein: The preparation process of the modified expansion matrix material is as follows: S1.1, adding acrylic acid monomer to deionized water to prepare a hydrophilic acrylic acid solution, wherein the mass fraction of the acrylic acid monomer in the acrylic acid solution is 20%-60%; S1.2, weighing a crosslinking agent and an active initiator, wherein the crosslinking agent is one or more of trimethylolpropane trimethacrylate, 1,4-butylene glycol diacrylate, ethylene glycol dimethacrylate, and N,N-methylenebisacrylamide, and the amount of the crosslinking agent is 0.2%-0.8% of the mass of the acrylic acid solution, and the amount of the active initiator is 0.2%-0.5% of the mass of the acrylic acid solution; adding the crosslinking agent to the acrylic acid solution in step S1.1, and passing nitrogen gas at a uniform speed to deoxygenate, stirring evenly, adding the active initiator to carry out polymerization reaction, and obtaining a procolloid after the polymerization reaction is completed; S1.3, the pre-colloid obtained in step S1.2 is put into a meat grinder and ground, then an alkaline solution is weighed for neutralization, and then the product is sieved and placed in a drying oven for drying to further obtain pre-colloid polymer particles; S1.4, weighing a surface crosslinking agent, the amount of the surface crosslinking agent is 2%-5% of the pre-colloidal polymer particles, the surface crosslinking agent is a mixed aqueous solution of ethanol, polypropylene glycol, and diglycidyl ether, wherein the mass ratio of ethanol, polypropylene glycol, diglycidyl ether to water is 3-5:3-5:5-10; spraying the surface crosslinking agent on the surface of the pre-colloidal polymer particles obtained in step S1.3, stirring evenly, and then putting it into a drying oven for drying again to obtain an expanded matrix material; S1.5, weigh the natural polymer solution, the amount of which is 1%-5% of the expansion matrix material, and evenly spray the natural polymer solution with active hydrophilic groups on the expansion matrix material obtained in step S1.4, stir evenly and put it into a drying oven for drying again to obtain a modified expansion matrix material, and sieve the modified expansion matrix material of different particle sizes as needed for standby use; The preparation process of the cross-linking curing agent is as follows: S2.
1. Weigh the polyether polyol, place it in a rotary evaporator, and vacuum-dry it at 110-120°C until the water content is less than 0.05%, then take it out for later use; S2.2, weighing the chain extender, organic solvent, isocyanate, and catalyst, the amount of the chain extender is 8%-15% of the mass of the dehydrated polyether polyol, the amount of the organic solvent is 10%-30% of the mass of the dehydrated polyether polyol, the amount of the isocyanate is 20%-30% of the mass of the dehydrated polyether polyol, and the amount of the catalyst is 3%-5% of the mass of the dehydrated polyether polyol; the polyether polyol dehydrated in step S2.1 is added to a dry three-necked flask equipped with a magnetic stirrer, and the hydrophilic chain extender and the organic solvent are added under nitrogen protection and heating conditions of 50-80°C; after reacting for 30-60 minutes, isocyanate is added dropwise at a uniform speed, and the catalyst is added, and the reaction is continued for 8-15 minutes, and then an organic solvent is added again in an amount of 10%-30% of the mass of the dehydrated polyether polyol to obtain a system solution, at which time, the isocyanate content in the system solution is 5%-10%; S2.
3. Weigh a neutralizer in an amount of 3%-7% of the mass of the dehydrated polyether polyol; add the neutralizer to the system solution of step S2.2 under high shear force of a magnetic stirrer, adjust the system solution to an alkaline environment, and remove the residual organic solvent in the system solution after naturally cooling to 65°C under indoor conditions to obtain a cross-linking curing agent.
2. A composite material for grouting and plugging sudden water inrush in a karst pipeline according to claim 1, characterized in that: Execute step S1.2, wherein the active initiator is a redox initiator, including hydrogen peroxide and ascorbic acid in a mass ratio of 1:
2.
3. A composite material for grouting and plugging sudden water inrush in a karst pipeline according to claim 2, characterized in that: The polymerization reaction was carried out. When the solution temperature was between 85°C and 95°C and the temperature did not rise any more within 1 minute, the polymerization reaction was determined to be complete and a procolloid was obtained.
4. The composite material for grouting and plugging sudden water inrush in a karst pipeline according to claim 2, characterized in that: Execute step S1.3, wherein the alkaline solution is a sodium hydroxide solution, the mass fraction of sodium hydroxide in the sodium hydroxide solution is 20%-80%, and the degree of neutralization is 60%-90%; The temperature of the drying box is set at 110-130° C., and the drying time is set at 30 min-120 min.
5. The composite material for grouting and plugging sudden water inrush in karst pipelines according to claim 4, characterized in that: Execute step S1.4, the temperature of the drying oven is set at 110-130°C, and the drying time is set at 30min-120min.
6. The composite material for grouting and plugging sudden water inrush in karst pipelines according to claim 5, characterized in that: Execute step S1.5, the natural polymer solution is one or more of chitosan solution, guar gum, and gelatin; The temperature of the drying box is set at 110-130° C., and the drying time is set at 30 min-120 min.
7. The composite material for grouting and plugging sudden water inrush in karst pipelines according to claim 1, characterized in that: Execute step S2.1, wherein the polyether polyol is polyether polyol PEG1000 and polyether polyol PEG2000, and the mass ratio of the two is 1-5:1-5; The polyether polyol is placed in a rotary evaporator and dehydrated under vacuum at 110-120°C for 1.5-2h.
8. The composite material for grouting and plugging sudden water inrush in karst pipelines according to claim 7, characterized in that: Execute step S2.2, The chain extender is dimethylol propionic acid, The organic solvent is acetone solution. The isocyanate includes one or more of toluene diisocyanate, diphenylmethane diisocyanate, and hexamethylene diisocyanate. The catalyst is organotin.
9. The composite material for grouting and plugging sudden water inrush in karst pipelines according to claim 8, characterized in that: Execute step S2.3, add a neutralizing agent to the system solution of step S2.2 to make the pH value of the system solution between 8 and 9, wherein the neutralizing agent is triethylamine; After the system solution is naturally cooled to 65° C., the residual organic solvent in the system solution is removed by reduced pressure distillation to obtain a cross-linking curing agent.
10. A method for using a composite material for grouting and plugging sudden water in a karst pipeline, characterized in that: The grouting plugging composite material according to any one of claims 1 to 9 is used as follows: (1.1) Select modified expansive matrix materials of different particle sizes as needed and place them in the location of sudden water in the karst area. The modified expansive matrix materials respond to water and form a three-dimensional network structure skeleton, with the volume expanding by more than 300 times; or, (2.1) Weigh the modified expansion matrix material and the cross-linking curing agent in a mass ratio of 1-4:1-4, weigh anhydrous ethanol in a ratio of 5%-10% of the content of the cross-linking curing agent, and add the anhydrous ethanol into the cross-linking curing agent as a diluent; (2.2) The modified expansive matrix material is placed at the location where sudden water surge occurs in the karst pipeline or water seepage occurs in the lining cracks of the tunnel project. At the same time, the cross-linking curing agent added with anhydrous ethanol is pumped to the location where the modified expansive matrix material is placed. After the two are mixed, a physical cross-linking reaction occurs to form an agglomerated gel with the ability to resist piston-like sliding, namely, a grouting plugging composite material.
Citation Information
Patent Citations
Expanded polymer grouting material for high pressure and large flow karst water inrush treatment and preparation method
CN109535306A
Karst pipeline type ultrahigh-expansion grouting material for efficient blocking of gushing water, and preparation method, use method and application thereof
CN110835449A